Coeliac disease : investigation of the genetic factors underlying coeliac disease - Belzen, M.J. (Martine Juliana) van (My University, 2003)
Coeliac disease is a common food intolerance with a complex genetic aetiology. It is caused by ingestion of gluten peptides from wheat and related proteins from barley and rye in genetically susceptible individuals. The disease affects the small intestine and leads to abnormalities ranging from the infiltration of the villous epithelium by lymphocytes to total villous atrophy. Clinical symptoms include gastrointestinal complaints such as diarrhoea and abdominal pain but also fatigue, weight loss, anaemia, osteopenia, growth retardation and failure to thrive. Coeliac disease is treated by a life-long gluten-free diet; there is no drug therapy available. One important genetic factor contributing to coeliac disease is the human leukocyte antigen (HLA) DQ locus. The majority of patients are positive for DQ2, and almost all of the remaining patients are positive for DQ8. However, the contribution of the HLA region comprises at most half of the total genetic risk. Therefore, non-HLA genes must also play an important role in coeliac disease pathogenesis, but little is known about the location and identity of these genes. This thesis describes the first localisation of susceptibility loci for coeliac disease in the Dutch population, in a well-characterized set of affected sibpairs. Linkage analysis revealed that a major locus was located at 19p13.1. This is the first locus to reach genome-wide significance in coeliac disease in an outbred population. Another locus, showing genome-wide suggestive linkage, was identified at 6q21-22. This region is also implicated in other autoimmune disorders and it may therefore harbour a general susceptibility gene for autoimmunity. Both the 19p13.1 and 6q21-22 loci present novel susceptibility loci for coeliac disease. A second genome-wide screen was performed in a four-generation Dutch family with 17 coeliac disease patients. Surprisingly, a third locus, located at 9p21-13, was identified as the major locus in this family. This locus had also been implicated in Scandinavian families with coeliac disease, and probably presents a locus with a small risk to coeliac disease in general. The 19p13.1 candidate region of 3 Mb, containing 92 genes, was subjected to systematic fine-mapping. Association analysis using microsatellite markers narrowed-down the region to 450 kb and only 12 genes. Subsequent typing of single nucleotide polymorphisms pinpointed the location of the gene to the final 150 kb of this region, with eight possible candidate genes left. Furthermore, the contribution of three functional candidate genes to coeliac disease risk was evaluated: 1. tissue transglutaminase, which modifies gluten peptides into epitopes with strong affinity for HLA-DQ2 and DQ8, resulting in a greatly enhanced T cell response, 2. the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), which has been implicated as a general susceptibility gene for autoimmunity, 3. the cytokine interferon-?, which plays an important role in the pathogenesis of coeliac disease. However, none of these genes showed association with coeliac disease. Finally, an extensive scan of the HLA region was performed to search additional HLA risk loci for coeliac disease, acting independently of DQ2. The results indicated that the contribution of the HLA region is mainly attributable to DQ2 and that a significant contribution of other HLA genes is unlikely.
Keywords: Geneeskunde; coeliac disease; gluten-intolerance; complex disease; autoimmune disease; gastroenterology; linkage analysis; affected sibpair analysis; association analysis; human genetics; HLA-region